Menggali Potensi Keunggulan Bersaing Destinasi Wisata Alam Pegunungan di Lumajang - HESTI BUDIWATI (Jurnal Ilmu Manajemen Advantage, 2019)
This study aims to determine the potential for competitive advantage and weaknesses which is a priority improvement strategy to achieve excellence in B29 natural tourism in Lumajang. B29 nature tourism in Lumajang is located in Senduro District in Lumajang. By using lean six sigma data analysis techniques on 30 respondents, this study netted the opinions of respondents based on the perceptions, hopes and interests of the people who visited the natural tourism B29 in Lumajang. The questionnaire was first tested for validity and reliability. The results of the study found that the advantages possessed by B29 nature tourism are located at community friendliness, natural beauty and adventure opportunities, while the priority of improvement is the availability of medical assistance, public facilities, electricity, clean water and communication networks. Future research is expected to be able to research with the same method to find competitive advantage in other objects